Cloud observability in action - Hausenblas, Michael (Manning Publications, 2024)
Don't fly blind. Observability gives you actionable insights into your cloud native systems--from pinpointing errors, to increasing developer productivity, to tracking compliance. Observability is the difference between an error message and an error explanation with a recipe how to resolve the error! You know exactly which service is affected, who's responsible for its repair, and even how it can be optimized in the future. Cloud Observability in Action teaches you how to set up an observability system that learns from a cloud application's signals, logging, and monitoring, all using free and open source tools. In Cloud Observability in Action you will learn how to: Apply observability in cloud native systems Understand observability signals, including their costs and benefits Apply good practices around instrumentation and signal collection Deliver dashboarding, alerting, and SLOs/SLIs at scale Choose the correct signal types for given roles or tasks Pick the right observability tool for any given function Communicate the benefits of observability to management A well-designed observability system provides insight into bugs and performance issues in cloud native applications. They help your development team understand the impact of code changes, measure optimizations, and track user experience. Best of all, observability can even automate your error handling so that machine users apply their own fixes--no more 3AM calls for emergency outages. About the Technology Cloud native systems are made up of hundreds of moving parts. When something goes wrong, it's not enough to know there is a problem--you need to know where it is, what it is, and how to fix it. This book takes you beyond traditional monitoring, explaining observability systems that turn application telemetry into actionable insights. About the Book Cloud Observability in Action gives you the background and techniques you need to successfully introduce observability into cloud-based serverless and Kubernetes environments. In it, you'll learn to use open standards and tools like OpenTelemetry, Prometheus, and Grafana to build your own observability system and end reliance on proprietary software. You'll discover insights from different telemetry signals, including logs, metrics, traces, and profiles. Plus, the book's rigorous cost-benefit analysis ensures you're getting a real return on your observability investment. What's Inside Observability in and of cloud native systems Dashboarding, alerting, and SLOs/SLIs at scale Signal types for any role or task State-of-the-art open source observability tools About the Reader For application developers, platform owners, DevOps, and SREs. About the Author Michael Hausenblas is a Product Owner in the AWS Open Source Observability team. Quotes Incredible! This book gets you up to speed, and sets you up for the future. I was especially impressed with the depth and detail for continuous profiling, whose impact is only starting to be understood. - Frederic Branczyk, Polar Signals Pairs a wealth of knowledge on cloud native environments with best practices and insights into observability. A must-read for cloud engineers. - Daniel Gomez Blanco, Author of Practical OpenTelemetry Take the right steps to protect your precious infrastructure from those pesky outages and incidents. - Kit Merker, Nobl9 Does a fantastic job distilling the key concepts for cloud observability. An important guide for practitioners. - Ken Finnigan, Lumigo.
Online resource; title from title details screen (O'Reilly, viewed March 4, 2024)
Keywords: Cloud computing; Observers (Control theory); Infonuagique; Observabilité (Théorie de la commande); Audiobooks; Livres audio